Análise da acessibilidade de pessoas com deficiência física aos espaços de circulação de pedestre: o caso de Campinas-SP - Reis, Débora Feliciana dos (2014)
In this study the conditions of accessibility of pedestrian circulation spaces offered to people with physical disabilities users wheelchair were analyzed. The importance and influence of the characteristics of sidewalks and crossings in the choice of paths of public respondent were investigated. A virtual technical audit , through Google StreetView, paths frequently used, which had been previously evaluated and reported by respondents were analyzed . The virtual audit was based on the requirements of NBR9050/04, rules addressing accessibility for people with physical disabilities to buildings , spaces , urban furniture and equipment . First, related research were consulted and delimited the important and influential spaces for pedestrian movement characteristics, with respect, a person with physical disabilities. The results showed that the important characteristics in the sidewalks and crossings, and the quality of these reviews on the paths. The virtual audit showed the actual conditions of the pedestrian circulation spaces, which are outside the standards required by the standard, however the researched public was more tolerant conditions offered in these spaces.